Effect of polyethylene glycol and propyltrimethoxysilane on structural and optical properties of zinc oxide nanoparticles synthesized by sol–gel process - Djahnit Leila; López-González Mar; Belhadj Fatima; Naitbouda Abddelyamine; Benosmane Ali; Haddaoui Nacereddine (Journal of Theoretical and Applied Physics)
Abstract Zinc oxide nanoparticles (ZnO NPs) are prepared by sol–gel process, using both polyethylene glycol (PEG-400) as surfactant and propyltrimethoxysilane (PTMS) as capping agent. Surface modification is performed in situ procedure. The physical parameters such as strain and stress values are calculated via the Williamson–Hall plot (W&H) assuming a uniform deformation model (UDM) and uniform stress deformation model, and by the size and strain plot method (SSP). The results show that the crystallite size estimated from Scherrer’s formula, (W&H), (UDM), (SSP) and the particle size estimated from DSL are inter-correlated, which confirm the small size and the isotropic nature of our ZnO NPs. The FTIR spectroscopy illustrates that PEG-400 and PTMS could be adsorbed at the ZnO NPs surface. The distinct emission peak in the blue band is located at 490 nm and E 2 (high) mode is situated at 436 cm−1. Both results confirm the oxygen deficiency in the ZnO NPs.